Social Justice Accounting In An Islamic Perspective - Masradin; Alimuddin; Syarifuddin (JURNAL ECONOMINA, 2026)
This study aims to analyze how modern accounting practices in the retail sector in Makassar represent the value of social justice from an Islamic perspective. The study applies a qualitative approach using Critical Accounting and Islamic Accounting perspectives. Data were collected through in-depth interviews with accounting staff, human resource staff, contract workers, and operational retail workers. Data analysis was conducted using NVivo through thematic coding and word cloud visualization. The findings show that modern accounting practices remain dominated by profitability orientation, operational cost efficiency, and control over worker productivity. Accounting systems function as organizational surveillance instruments through sales targets, performance evaluations, and labor cost control. These practices contribute to work pressure, contract-based employment, and uncertainty in worker welfare. Islamic values such as al-'adl, amanah, and social responsibility are recognized as important moral principles, but they have not yet become the main orientation of modern accounting practices.